Toward multimodality oral cancer diagnosis in the XXI century: Blending cutting edge imaging and genomic/proteomic definition of suspicious lesions - Le, Anh (Biomedical Informatics, 2011)
If emergent genomic and proteomic approaches to early oral cancer detection are to be successful, a means of reliably and comprehensively identifying high-risk tissue sampling sites constitutes an essential step in the oral cancer screening process. Recent studies have determined that in vivo Optical Coherence Tomography (OCT) is a quick and user-friendly tool for detecting and mapping oral lesions, and that it can enhance diagnostic accuracy when using high resolution diagnostic techniques such as in vivo microscopy. Therefore OCT can potentially provide a means of improving the clinical usefulness of novel diagnostic approaches such as proteomics by identifying sites that need to be sampled.